Improvement of the impact resistance of natural fiber–reinforced polypropylene composites through hybridization. (5th April 2021) - Várdai, Róbert; Lummerstorfer, Thomas; Pretschuh, Claudia; Jerabek, Michael; Gahleitner, Markus; Bartos, András; Móczó, János; Anggono, Juliana; Pukánszky, Béla
Abstract: Polypropylene (PP) hybrid composites were prepared by the combination of natural reinforcements and poly(ethylene terephthalate) (PET) fibers. Wood, flax, and sugar palm fibers were used to increase stiffness and strength, while PET fibers served to improve impact resistance. Interfacial adhesion was increased by using a maleated PP (MAPP) coupling agent. The hybrid composites containing 20 wt% of the natural fibers were homogenized in a twin‐screw compounder and then injection molded into standard tensile specimens. The amount of PET fibers was changed from 0 to 40 wt% in the composites. Tensile and impact testing, acoustic emission measurements, and scanning electron microscopy (SEM) were used for the characterization of the composites as well as to follow deformation and failure processes. The results proved that the concept of using PET fibers to improve impact resistance works with all natural fibers. Local deformations, the debonding or pullout of the PET fibers, initiate the plastic deformation of the matrix, which consumes considerable energy. The fracture of PET fibers might also contribute to energy absorption. The type of natural fiber does not influence the effect; the amount of PET fibers determines fracture resistance. The improvement of interfacial adhesion by coupling increases strength and slightly improves impact resistance. The overall properties of the hybrid composites prepared are acceptable, sufficiently large stiffness and impact resistance being achieved for a large number of structural applications.